1998
DOI: 10.1074/jbc.273.47.31209
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Folate-binding Site of Human Thymidylate Synthase by Site-directed Mutagenesis

Abstract: Human thymidylate synthase (TS) contains three highly conserved residues Ile-108, Leu-221, and Phe-225 that have been suggested to be important for cofactor and antifolate binding. To elucidate the role of these residues and generate drug-resistant human TS mutants, 14 variants with multiple substitutions of these three hydrophobic residues were created by site-directed mutagenesis and transfected into mouse TS-negative cells for complementation assays and cytotoxicity studies, and the mutant proteins expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
2
13
1
Order By: Relevance
“…For instance, Ile108Ala produced marked resistance to ZD1694 and AG337, with lesser resistance to GW1843U89. A Phe225Trp mutation produced 17-fold resistance to the latter compound and about half the level of resistance to fluorouracil, without any increase in the IC 50 , or the kinetics of enzyme inhibition by ZD1694 and AG337 (Tong et al, 1998b). As observed for DHFR, mutations in TS that arise during selection can be accompanied by amplification of the enzyme, probably required for sufficient catalytic activity for the natural substrate to sustain cell replication (Tong et al, 1998a).…”
Section: Alterations In Tsmentioning
confidence: 99%
“…For instance, Ile108Ala produced marked resistance to ZD1694 and AG337, with lesser resistance to GW1843U89. A Phe225Trp mutation produced 17-fold resistance to the latter compound and about half the level of resistance to fluorouracil, without any increase in the IC 50 , or the kinetics of enzyme inhibition by ZD1694 and AG337 (Tong et al, 1998b). As observed for DHFR, mutations in TS that arise during selection can be accompanied by amplification of the enzyme, probably required for sufficient catalytic activity for the natural substrate to sustain cell replication (Tong et al, 1998a).…”
Section: Alterations In Tsmentioning
confidence: 99%
“…5 Our laboratory has previously generated a variety of drug resistance genes, and combinations thereof, conferring resistance to antimetabolites such as MTX, trimetrexate, 5FU, raltitrexed, thymitaq, and cytosine arabinoside. 14,[20][21][22][23][24] In this study, we show that the transfer of a DHFR F/S-TS G52S fusion gene into hematopoietic progenitor cells results in resistance to a promising new antifolate, pemetrexed.…”
Section: Discussionmentioning
confidence: 94%
“…Refs. [5][6][7][8]. Here, we used a different strategy, based on the hypothesis that amino acid replacements yielding 5-FdUR resistance are located throughout the TS primary sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of a drug-resistant TS into bone marrow stem cells could protect patients from the severe side effects of TS inhibitors. Based on this premise, mutations have been identified that render human TS resistant to 5-fluoropyrimidines and anti-folate analogs (5)(6)(7)(8)(9)(10). Nearly all of these mutations map within the catalytic site.…”
mentioning
confidence: 99%
See 1 more Smart Citation